A promising CoFeNi2V0.5Mo0.2 high entropy alloy with exceptional ductility. (May 2019) - Jiang, L.; Lu, Y.P.; Song, M.; Lu, C.; Sun, K.; Cao, Z.Q.; Wang, T.M.; Gao, F.; Wang, L.M.
Abstract: A novel high entropy alloy with the composition of CoFeNi2 V0.5 Mo0.2, shows unusual strain hardening ability and an excellent combination of ductility and strength. Especially at 873 K, the elongation can reach 189.2%, almost three times that of the common high temperature alloys. Microstructural characterization suggests a coexistence of planar slip and cross slip. The resistance of planar slip serves to strengthen the alloy, while the cross slip effectively relieves strain concentration, substantially contributing to the uniform elongation. Also, the interaction of planar slip and cross slip will lead to the formation of two kinds of dislocation loops. Graphical abstract: Unlabelled Image